Fostering Advanced Mathematical Thinking through Islamic Ethical Integration in Elementary Classrooms to Support Sustainable Development Goals (SDGs) - Nadya Dewinda Agustin; Mohamad Syarif Sumantri; Arita Marini (ASEAN Journal of Educational Research and Technology, 2026)
This study investigates the potential of integrating Islamic ethical values into heuristic problem-based learning to foster Advanced Mathematical Thinking (AMT) skills among Islamic elementary students. Using an explanatory sequential mixed-methods design, the research involved 120 fifth-grade students from Madrasah Ibtidaiyah in a metropolitan city in Indonesia. The intervention employed the Heuristic Problem-Based Learning integrated with the Triplet Structure Model (HPbLTSM), emphasizing deep learning through inquiry, abstraction, representation, creativity, and proof. Results show that students with strong mathematical dispositions significantly improved their AMT skills, while even those with weaker dispositions benefited when ethical and collaborative frameworks were embedded. The study demonstrates that AMT is not exclusive to mathematically gifted students and that integrating Islamic values (such as ta’adub, musāwah, and taṭawwur wa ibtikār) enhances cognitive, ethical, and social growth. The findings align with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions).